2019
DOI: 10.3389/fimmu.2019.00997
|View full text |Cite
|
Sign up to set email alerts
|

Immune Differentiation Regulator p100 Tunes NF-κB Responses to TNF

Abstract: Tumor necrosis factor (TNF) is a pleiotropic cytokine whose primary physiological function involves coordinating inflammatory and adaptive immune responses. However, uncontrolled TNF signaling causes aberrant inflammation and has been implicated in several human ailments. Therefore, an understanding of the molecular mechanisms underlying dynamical and gene controls of TNF signaling bear significance for human health. As such, TNF engages the canonical nuclear factor kappa B (NF-κB) pathway to activate RelA:p50… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Despite being apparently functionally normal in young mice, the Nfkb2 −/− Tregs in our study do show some altered characteristics reported previously as well, namely, reduced levels of CTLA-4 and enhanced GITR levels possibly related to heightened noncanonical NF-κB signaling 48,71 . It has been shown earlier that an absence of Nfkb2-p100 provokes enhanced RelB:p50 activity via the canonical NF-κB pathway in mouse embryonic fibroblasts, and that RelB:p50 induces a distinct set of genes, which are not activated by RelA:p50 and are associated with cell survival and cell division 72 . Our biochemical analyses revealed heightened nuclear activity of RelB:p50 in functionally normal Nfkb2 −/− Tregs, while our global transcriptomic studies established an altered gene expression pattern in them favoring pro-survival and pro-proliferative functions.…”
Section: Discussionmentioning
confidence: 96%
“…Despite being apparently functionally normal in young mice, the Nfkb2 −/− Tregs in our study do show some altered characteristics reported previously as well, namely, reduced levels of CTLA-4 and enhanced GITR levels possibly related to heightened noncanonical NF-κB signaling 48,71 . It has been shown earlier that an absence of Nfkb2-p100 provokes enhanced RelB:p50 activity via the canonical NF-κB pathway in mouse embryonic fibroblasts, and that RelB:p50 induces a distinct set of genes, which are not activated by RelA:p50 and are associated with cell survival and cell division 72 . Our biochemical analyses revealed heightened nuclear activity of RelB:p50 in functionally normal Nfkb2 −/− Tregs, while our global transcriptomic studies established an altered gene expression pattern in them favoring pro-survival and pro-proliferative functions.…”
Section: Discussionmentioning
confidence: 96%
“…NFKB2 has frequent mutations in cancers, and it is related with abnormal TNF signal transduction and tumor diseases. 20 Moreover, NFKB2 is a target of MYC suppression. NFKB2 deficiency can accelerate the development of lymphoma in Eμ‐myc transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…These events are triggered by many incentives related with many biological processes including inflammation, immunity, cell differentiation, cell cycle, tumor initiation, and cell apoptosis. NFKB2 has frequent mutations in cancers, and it is related with abnormal TNF signal transduction and tumor diseases 20 . Moreover, NFKB2 is a target of MYC suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Various lymphomas and leukemias, such as B cell chronic lymphocytic leukemia, multiple myeloma, and adult T-cell leukemia/lymphoma, have mutations in the nfkb2 gene, which encodes the protein p100 (56)(57)(58). Total loss of p100 in both knockout cell lines and multiple myeloma cells prolongs the NF-κB response to stimuli, providing a pro-survival response (30,59).…”
Section: Nfkb2-truncation Cancersmentioning
confidence: 99%